Infant, Maternal, and Neighborhood Predictors of Maternal Psychological Distress at Birth and Over Very Low Birth Weight Infants' First Year of Life. Issue 8 (October 2019) - Greene, Michelle M.; Schoeny, Michael; Rossman, Beverly; Patra, Kousiki; Meier, Paula P.; Patel, Aloka L.
Abstract: Objective: To use a social-ecological conceptualization to analyze change of maternal distress, defined as depression, anxiety, and perinatal-specific post-traumatic stress (PPTS), across very low birth weight (VLBW) infants' first year of life and to identify infant, maternal, and neighborhood predictors of these changes over time. Methods: Mothers of VLBW infants (n = 69) completed psychological distress questionnaires 2 to 4 weeks after infant birth, 2 weeks before infant discharge from neonatal intensive care unit, and at infants' 4- and 8-month corrected age (age adjusted for prematurity). Infant and maternal sociodemographic data were collected from medical chart review. Neighborhood data were obtained through US census data. Multilevel linear growth modeling was used to (1) predict unstandardized estimates of mothers' initial levels of depression, anxiety, and PPTS at the time of infant's birth and the rate of change of these markers of distress over time and (2) model unstandardized estimates of infant, maternal, and neighborhood as predictors of distress at infants' birth and change over time. Results: Unstandardized estimates from multilevel linear growth modeling revealed depression (−2.8), anxiety (−1.4), and PPTS (−0.7) declined over infants' first year of life (<0.001). Mothers residing in lower-income homes and neighborhoods, respectively, reported lower anxiety (−11.2, p = 0.03) and PPTS (−31.1, p = 0.01) at infant birth. Greater infant birth weight predicted both lower anxiety (−0.02, p = 0.02) and lower PPTS (−0.02, p = 0.005). Conclusion: Mothers psychologically recover over VLBW infants' first year of life. Results add to a building literature about socioeconomically disadvantaged mothers of preterm infants, reporting lower distress; this warrants additional research.